2023
DOI: 10.1161/circresaha.122.321542
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Macrophage mTORC2 Drives Atherosclerosis via FoxO1 and IL-1β Signaling

Abstract: Background: The mTOR (mechanistic target of rapamycin) pathway is a complex signaling cascade that regulates cellular growth, proliferation, metabolism, and survival. Although activation of mTOR signaling has been linked to atherosclerosis, its direct role in lesion progression and in plaque macrophages remains poorly understood. We previously demonstrated that mTORC1 (mTOR complex 1) activation promotes atherogenesis through inhibition of autophagy and increased apoptosis in macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“… 48 Consistent with our previous study, 17 , 44 direct mTOR inhibitors, such as rapamycin, have been shown to promote autophagy and reduce apoptosis, thus stimulating HSCs activation, thereby promoting liver fibrosis. 49 , 50 Here, we identified the downstream signaling pathway PI3K/AKT/mTOR by which BMSCs regulate HSCs autophagy. As expected, our results showed that BMSCs activated PI3K/AKT/mTOR pathway to inhibit the HSCs autophagy and activation.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Consistent with our previous study, 17 , 44 direct mTOR inhibitors, such as rapamycin, have been shown to promote autophagy and reduce apoptosis, thus stimulating HSCs activation, thereby promoting liver fibrosis. 49 , 50 Here, we identified the downstream signaling pathway PI3K/AKT/mTOR by which BMSCs regulate HSCs autophagy. As expected, our results showed that BMSCs activated PI3K/AKT/mTOR pathway to inhibit the HSCs autophagy and activation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β response is a crucial inflammatory pathway of foam cells involved in AS progression, which promotes the expansion of AS lesion areas along with PDGF, TNF, and M-CSF ( 95 ). Zhang et al reported that the lack of mTORC2 in macrophages significantly increased FoxO1-mediated IL-1β response and aggravated AS progression ( 11 ). Mature macrophages are important sources of foam cells.…”
Section: Atherosclerosis-related Tfsmentioning
confidence: 99%
“…Cell cycle regulation related TF FoxM1 promotes the proliferation of SMCs and ECs to intensify vascular remodeling ( 10 ). FoxO1 exacerbates the inflammatory response and promotes foam cell formation in response to cell stimulation, thereby exacerbating atherosclerotic lesions ( 11 ). The complete comprehension of the role of TFs in vascular diseases poses two significant challenges.…”
Section: Introductionmentioning
confidence: 99%